New design of a linear double-sided printed dipole array based on bat algorithm for interference suppression in the first sidelobe direction - Truong, Luong Xuan; Vu-Bang Giang, Truong; Tuan, Tran Minh (IET microwaves, antennas & propagation, 2020)
This study proposes a design of a double-sided printed dipole (DSPD) antenna array with a low first sidelobe level (FSLL) for interference suppression. The proposed array consists of ten DSPD antennas based on the Rogers RO4003C substrate (ɛr = 3.55). The FSLL has been compressed by imposing a single null at the centre of the first sidelobe. The excitation power distribution of the array has been calculated by using the bat algorithm with the amplitude-only control technique and has been implemented by a series-fed network. A back reflector, which is based on an FR4 substrate (ɛr = 4.4), has been used to improve the maximum gain. The simulation results show that the FSLL can be reduced with a null deep level (NDL) of −40 dB in the E-plane at the frequency of 3.5 GHz, while the maximum gain of the array is around 17.7 dBi, and the bandwidth is 600 MHz (3.3–3.9 GHz) with −10 dB of S11. A prototype of the proposed DSPD antenna array has been fabricated and measured. A good agreement can be achieved between simulation and measurement results.